Pemberdayaan Masyarakat di Desa Pearung Melalui Pelestarian Wisata Alam Geosite Sipinsur - Lela Siska Inriani Samosir (Jurnal Magistra, 2023)
Community empowerment in Pearung Village through preserving the Sipinsur Geosite is part of tourism development efforts. This research uses a literature detective method and the author reveals that the search for economic and social potential resulting from the management of natural resources and the tourism sector in an area. Indonesia as a country rich in natural resources has great potential to improve its economy and regional growth through tourism development. Pearung Village in Humbang Hasundutan Regency, North Sumatra, is a clear example of how the use of the Sipinsur Geosite is an initiative in tourism development. This not only creates an attraction for visitors but also empowers local communities. The government has an important role in supporting community empowerment through education, training and infrastructure improvement programs. The impact can be seen in economic growth, improving the quality of life, and infrastructure development in Pearung Village. Tourism development not only increases the number of tourists, but also brings significant changes in the daily lives of residents, such as improving the agricultural sector and improving infrastructure.